A Reassessment of the Relationship between International Reference Preparations for Human and Rabbit Thromboplastins - van den Besselaar, M. H. P. A.; Tripodi, A. (Thrombosis and Haemostasis, 2002)
Two established international reference preparations (IRP) for thromboplastins, i.e. RBT/90 (rabbit, plain) and rTF/95 (recombinant human, plain) have been calibrated against each other in a 7-centre exercise performed in 2000. The purpose of the study was to compare the calibration results with those of the original calibration study performed in 1995. The international sensitivity index (ISI) for rTF/95 was calculated relative to the ISI for RBT/90. The mean ISI for rTF/95 was 0.961 (between-lab SD 0.028) which was 2% greater than the historical value determined in 1995. There is no indication that the two IRP have deteriorated, but further monitoring of the calibration relationship is recommended.
Keywords: International sensitivity index; prothrombin time; thromboplastin